Solar heat absorbing coating from multi-walled carbon nanotube composites with linear low-density polyethylene-coated copper sheet - Samor Boonphan (2018)
© SAGE Publications. This study aims to investigate the effects of multi-walled carbon nanotubes (MWNTs)/linear low density polyethylene composite-coated copper sheets on an energy conversion efficiency of a solar water heating system. Volume percentages of 1, 3 and 5 MWNTs were ball-mill mixed with linear low density polyethylene before using a hot press method to coat the composites. A bonding layer between the composites and the copper sheets was intercalated using MWNTs/polyvinyl butyral composites. The strength of the bonding layer was tested using a shear tension test. Microstructures of the composites were observed by scanning electron microscopy. The energy conversion efficiency and solar absorptance of the solar heat absorbing coatings were measured by a home-made method and ultraviolet visible spectroscopy, respectively. The results showed that the efficiency and the absorptance increased by 40% and 0.95, respectively with the increasing volume percentages of MWNTs up to 5 vol.% in linear low density polyethylene.